Penerapan Prinsip–Prinsip Hukum untuk Mematuhi Undang–Undang dalam Kasus Pencurian Data Pribadi Pinjaman Online (Pinjol): Ayni Suwarni Herry - Ayni Suwarni Herry (Samudra Publisher, 2024)
The existence of the Online Borrowing platform (PINJOL) has made it easier to access sources of funds, but has also had a negative impact on the security of personal data. In this case, the Information and Electronic Transactions Law (UU ITE) is the legal basis that regulates the protection of personal data in Indonesia. This research aims to analyze the application of legal principles in handling cases of personal data theft that occurred on one of the PINJOL platforms, focusing on compliance with the ITE Law regulations. Through the case from the news